Amarium : una antología emocional (2017)
Amarium is an editorial project that seeks to redefine the meaning of collecting by showing the subjective value of collections and the important role that objects have in the creation of emotions, relationship mediation and the containment of memories. Its aim is to generate empathy and a certain degree of identification between the audience and the collectors, showing the emotional bonds between each piece and its owner, allowing the reflection that we are all collectors.--Tomado del Formato de Documento de Grado.